Investigation of Elastic Energy on Single Crystal GaN Nanobeams with Different Span - Shang-Chao Hung; Cheng-Fu Yang; Yi-Cheng Hsu (International Journal of Photoenergy)
This research presents a novel technique which can more efficiently fabricate different spans of nanobeams on the same substrate. It requires less time to prepare specimen and further shortens the process of aligning, clamping, and testing. Also, we probe into the elastic deformation properties of clamped freestanding GaN nanobeams with different spans. In the bending process, displacement, D, corresponding to load, P is strongly dependent on the span of nanobeam at the same penetration depth and a distinct linearity is observed. Young’s moduli E of the GaN in this study are calculated as 171.3 GPa ±5.4% and 264.2 GPa ±4.7% by strain energy methods, respectively, for the longer and shorter spans of nanobeams, serving as a simple supporting beam of elastic material under small deformation. The result shows that, even under small deformation, the rigidity enhancement helps the shorter nanobeam store more elastic energy.